Building Brand Image Through Community Development: Qualitative Study on Rubi Community and Avoskin - Elke Alexandrina; Novrita Widiyastuti; Gabrielie Maria Clarenzha; Johan Adham Putranto (Green Publisher Indonesia, 2026)
The beauty industry in Indonesia has experienced rapid growth, leading to increased competition, particularly among local brands striving to enhance their brand image and foster consumer loyalty. Avoskin, a local beauty brand that adopts the concept of green beauty, launched the RUBI Community as a platform for women's empowerment through a community development approach. This programme aims to strengthen emotional connections with consumers through four main pillars: sustainability, empowerment, entrepreneurship, and creativity. This research aims to analyse the contribution of the RUBI Community in shaping Avoskin's brand image and to provide strategic recommendations on applying community development as an alternative approach to building a strong brand image. A qualitative approach using a narrative review method is employed to provide an in-depth understanding of the interactions between community members and the Avoskin brand. Secondary data were obtained through document analysis related to community activities. The research is expected to generate insights into the effectiveness of community development in strengthening Avoskin's brand image, as well as providing strategic recommendations for other local brands seeking to enhance their brand image. Community development can be an effective approach to building strong emotional connections with consumers and reinforcing a brand image through the values of sustainability, empowerment, entrepreneurship, and creativity.